2009
DOI: 10.1002/cjce.20218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbonisation on selected engineering properties of carbon resin electrodes for electrochemical treatment of wastewater

Abstract: In this study, effects of selected factors on selected properties of carbon resin electrodes (CRE) have been investigated. CRE were developed from used dry cells and resin using non-heat-treatment process. Selected properties (density, electrical resistance, microstructure, hygroscopy, stability moisture content, compressive and flexural strength) of the electrodes were monitored and effects of carbonisation temperature, carbon particle size, and compaction pressure on these properties were studied.The study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…3b revealed that at a fixed percentage binder and compaction pressure, swelling of the graphite electrode decreases with increasing particle sizes, which can be attributed to higher binding forces within the higher particle size. These relationships are similar and agreed with observations made in the literature [15] on the stability and the progress of Carbon-Resin utilized in the reduction of chloride in salty water [21] on the swelling property and mechanism of lithium iron phosphate cell at extreme-temperature preservation, [20] on the improved swelling behaviour of Li-ion cells at the anode, [16] on the stability and thermal properties of carbon composite electrodes produced for as a facility during the treatment of raw water and industrial wastewaters electrochemically, [15] on the utilization Of Weibull Techniques to express the effective distribution of carbon composite electrodes and [15] on characterization and durability of a composite of carbon mixed with resin electrode. [15] on the swelling phenomenon in Lithium-ion power cells, [17] on the regulated swelling behaviour and an effective cycle of silicon mixed graphite composite cells for high density of energy in lithium-ion cells, [18] on the 2 k laboratory scale factorial experiments on operational factors that impacted the efficacy of carbon mixed with resin electrodes.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…3b revealed that at a fixed percentage binder and compaction pressure, swelling of the graphite electrode decreases with increasing particle sizes, which can be attributed to higher binding forces within the higher particle size. These relationships are similar and agreed with observations made in the literature [15] on the stability and the progress of Carbon-Resin utilized in the reduction of chloride in salty water [21] on the swelling property and mechanism of lithium iron phosphate cell at extreme-temperature preservation, [20] on the improved swelling behaviour of Li-ion cells at the anode, [16] on the stability and thermal properties of carbon composite electrodes produced for as a facility during the treatment of raw water and industrial wastewaters electrochemically, [15] on the utilization Of Weibull Techniques to express the effective distribution of carbon composite electrodes and [15] on characterization and durability of a composite of carbon mixed with resin electrode. [15] on the swelling phenomenon in Lithium-ion power cells, [17] on the regulated swelling behaviour and an effective cycle of silicon mixed graphite composite cells for high density of energy in lithium-ion cells, [18] on the 2 k laboratory scale factorial experiments on operational factors that impacted the efficacy of carbon mixed with resin electrodes.…”
Section: Resultssupporting
confidence: 91%
“…Composite electrodes (carbon-resin or graphite-resin electrodes) were produced from used and discarded primary cells. The details of the development are presented in previous articles such as Oke et al [15], Oke et al [16] and Oke [21]. The equipment used is presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakdown is as adapted from Grover and Mishra 23 and Oke. 24 It was modified to suit the present purpose.…”
Section: Cost Analysismentioning
confidence: 99%